(untitled) (Revista de Investigaciones Universidad del Quindío, 2020)
The first antecedents of the principle of relativity in Mexico are found in a project for the Constitution of the State of Yucatán in 1840 by the jurisconsult Manuel Crescencio Rejón where a system is introduced that allows the control of the constitutionality lato sensu (to all acts considered constitutional law) by judicial bodies using for the first time the term “protect” when an activity that was contrary to the Constitution was annulled by resolution. Therefore, this document provides the reader with an outline regarding the principle of relativity and general declaration of unconstitutionality, which sets out elements to consider for the good administration of justice in the Mexican state.